Performance dynamics in professional padel: winners, forced errors, and unforced errors among men and women players - Conde-Ripoll, R.; Martín-Miguel, I.; Muñoz, D.; Escudero-Tena, A. (International Journal of Performance Analysis in Sport, 2025)
The study aimed to analyse the number of satisfactory shots, the effectiveness of the last shot, and the winners, forced errors, and unforced errors in men`s and women`s professional padel. Data were collected from 41 professional matches at the World Padel Tour Finland Padel Open tournament, focusing on variables such as "set result, effectiveness and typology of the last shot, and number of successful shots". Descriptive and inferential analyses, including chi-square tests and Z-tests with Bonferroni corrections, were performed. Results indicate that in the men`s padel, the serving pair wins more points than the returning pair. Similarly, in the women`s padel, the serving pair generally wins more points, but in long rallies (20+ shots), the returning pair wins slightly more. A significant association exists between the type of shot and its effectiveness in both winning and losing pairs (p < 0.001). In both men`s and women`s padel, smashes (24.6%-45.7%), bandejas (12.6%-20.2%), and volleys (24.0%-36.0%) are the most effective shots to secure winners. Backhand volleys (18.3%-25.1%) account for the most forced errors, while the most unforced errors are made with bandejas (19.2%-27.0%). These findings are crucial for coaches and players, helping to tailor training to improve match performance based on shot type and sex.